2019
DOI: 10.1007/s11089-019-00866-5
|View full text |Cite
|
Sign up to set email alerts
|

What Helps Christians Grow? An Exploratory Study Distinguishing among Four Distinctive Pathways

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In their exploratory study, Francis, Foster, Lankshear, and Jones (2019) identified two scales that served as indicators of growth in Christian discipleship. The first scale of seven items was identified as assessing depth of discipleship and styled Index of Depth of Discipleship.…”
Section: Measuring Growth In Discipleshipmentioning
confidence: 99%
See 4 more Smart Citations
“…In their exploratory study, Francis, Foster, Lankshear, and Jones (2019) identified two scales that served as indicators of growth in Christian discipleship. The first scale of seven items was identified as assessing depth of discipleship and styled Index of Depth of Discipleship.…”
Section: Measuring Growth In Discipleshipmentioning
confidence: 99%
“…In their exploratory study, Francis, Foster, Lankshear, and Jones (2019) set out to identify distinctive pathways by which the 1,123 participants had 'been helped in their journey of faith'. Factor analysis, employing principal component and varimax rotation, identified a clear four-factor structure.…”
Section: Identifying Pathways To Growthmentioning
confidence: 99%
See 3 more Smart Citations